Microalgae precipitation in treatment chambers during pulsed electric field (PEF) processing. (October 2016) - Straessner, Ralf; Silve, Aude; Eing, Christian; Rocke, Sarah; Wuestner, Ruediger; Leber, Klaus; Mueller, Georg; Frey, Wolfgang
Abstract: Pulsed electric field (PEF) treatment of microalgae has been demonstrated to exhibit processing advantages compared to conventional processing. Besides low specific energy requirements, PEF treatment can separate microalgae biomass into aqueous and oleaginous fractions. To minimize processing energy demand, the treatment of pre-concentrated microalgae suspensions is advantageous. For suspensions with a biomass density of approximately 80 g of dry weight per liter, microalgae precipitation at the electrodes of cross-linear treatment chambers was observed. This phenomenon is examined using the microalgae species Chlorella vulgaris and Auxenochlorella protothecoides . An interrelation between pH and zeta potential on the one hand and the amount of precipitated microalgae on the electrodes on the other hand is emerging. Impact of electric pulse parameters and pH was investigated and suggested that precipitation is caused by electrophoretic forces. The results indicate that shorter pulses can be used to reduce the unwanted precipitation. Industrial relevance: The manuscript describes an undesirable effect occurring while performing pulsed electric field (PEF) treatment on microalgae. We have indeed observed that microalgae tend to precipitate on the surface of the treatment electrodes during PEF processing. This precipitation of microalgae results in the distortion of the flow through the treatment chamber and in the modification of the electric field distribution. At an industrial scale, this will affect the process efficiency and therefore increase processing costs. In the worst case, the affected electroporation reactors might be blocked and require additional maintenance, generating extra costs. We demonstrate that the precipitation is induced by the interaction between the electric field and the surface-charged algae. Driving parameters for the precipitation effect were identified and strategies to avoid it are proposed in the manuscript. Highlights: PEF treatment induces precipitation of microalgae on the electrodes. Precipitation occurs predominantly at the anode. Precipitation is caused by electrophoretic forces imposed on negatively charged algae. Short pulses contribute to avoid or reduce precipitation on electrodes.